Acne caused by ziprasidone in a young patient with bipolar disorder: A case report - Yuan, Yiwen; Li, Xiaoqing; Jiang, Xingmei; Li, Zhixiong; Ou, Ying; Li, Zhe (Frontiers in Psychiatry, 2022)
Ziprasidone is a second-generation antipsychotic drug commonly used to treat schizophrenia and bipolar disorder. Acne is a common inflammatory disease of sebaceous glands in adolescents that is often co-morbid with anxiety and depression, which may reduce treatment compliance. Through unknown mechanisms, ziprasidone may cause a range of inflammatory responses. Whether ziprasidone can cause acne in young patients with bipolar disorder has not been reported.We report a 23-year-old woman with a 5-year history of bipolar disorder who experienced acne during use of ziprasidone. She was admitted to our hospital during one-month aggravation of her symptoms and was diagnosed as bipolar I disorder (current or most recent episode of depression), with psychotic features. She was given ziprasidone and soon developed acne, although she had never had a history of acne; the rash worsened substantially when the ziprasidone dose was increased. At the same time, levels of inflammatory factors increased. The rash resolved after ziprasidone therapy was stopped. When prescribing ziprasidone to young people with bipolar disorder, clinicians should consider the potential for adverse skin reactions. It may be useful to assay levels of inflammatory markers during ziprasidone therapy and adjust the dose if necessary in order to ensure treatment compliance.